Tingkat Pengetahuan dan Sikap Ibu dalam Pemberian Bakso Belut untuk Pencegahan Stunting pada Balita - Zarkasyi R, Rahmat; Usman, Usman; Hasyuti, Nur; Thasim, Sukmawati; Rahman, Abdul; Sudirman, Sudirman (FAKULTAS ILMU KESEHATAN UNIVERSITAS MUHAMMADIYAH PAREPARE, 2024)
The problem of stunting is still the most serious threat to toddlers in Indonesia. Nutritional problems in toddlers need to be handled properly because they have the potential to cause high mortality rates. Fulfillment of micronutrient needs can be obtained from food, fortified foods and direct supplementation. The purpose of the study was to determine the level of knowledge and attitudes of mothers in Providing Eel Meatballs to Prevent Stunting in Toddlers. The type of research used in this study is quantitative with a descriptive approach. This research was conducted in Parepare City for 3 months, namely February - April 2024. The sample of this study was 124 mothers of toddlers who were used as respondents with a data collection technique, namely Probability Sampling with a Simple Random Sampling approach. The results of the study showed that the majority of mothers' knowledge levels in providing Eel Meatballs to prevent stunting were in the good category, namely 55.65% and only 14.51% stated that they were lacking. In addition, the majority of mothers' attitudes in providing Eel Meatballs to prevent stunting were in the good category, namely 50.81% and only 12.90% stated that they were lacking. The conclusion of the study is that the level of knowledge and attitudes of mothers regarding giving eel meatballs to prevent stunting in toddlers is in the good category